Study of adsorption isotherms and kinetics models for lead ions removal from simulated wastewater using three-dimensional, printed water-filtration system with synthesized α-Fe2O3 - Hammood, Noor M.; Abdulrazzaq, Nada N.; Akrouti, Inen (Iraqi Journal of Chemical and Petroleum Engineering, 2024)
In this study, lead ions were removed from simulated wastewater by batch adsorptive filtration. A three-dimensional printed water filtration was designed using a blender and successfully synthesized from a PLA spool and a 3d printer machine. The filter surface was treated with NaOH solution to hydrolyze the polyester group in PLA. After that, α-Fe2O3 was prepared by the coprecipitation method and coated on the filter through doping and drying. α-Fe2O3 was characterized by X-ray diffraction (XRD), Energy-dispersive X-ray spectroscopy (EDX), and Brunauer-Emmet-teller (BET). The results successfully indicate the synthesis of α-Fe2O3 consisting of 67.3% Fe and 32.7% O2. α-Fe2O3 appeared to have a surface area of 95 m²/g with distinct morphology and functional group. The effect of initial Pb concentration (100-800) ppm and the effect of contact time (5-120) min on the removal process were studied. Lab data was collected, and the adsorption was investigated kinetically. The 3d printed filter system coated by iron oxide showed significant and promised results for wastewater treatment and lead ions removal using this technique. Also, the results showed that the adsorption of Pb ions on the α-Fe2O3 surface fitted with the Langmuir model, with a correlation coefficient (R²) of 98.65%. The kinetic model’s investigations revealed that the pseudo-second-order model was the most fitted model for the process with R² of 99.997%. The highest adsorption saturation capacity was 165.2 mg/g adsorbent.